Communication Strategies Employed by EFL Learners in A Speaking Class - Syarifudin Syarifudin; Nur Mukminatien; Sri Rachmajanti; Achmad Effendi Kadarisman (Universitas Negeri Malang, 2016)
Abstract: The present study explored verbal and nonverbal communication strategies (CSs) employed by learners both as message senders (speakers) and as message receivers (listeners) in English in a speaking class. It employed a qualitative design with an ethonography of communication approach in a limited situation setting (speaking class). Thirty two students taking Speaking II subject at the English Education of IKIP Mataram were selected by using a purposeful technique. The techniques used to collect data consisted of non-participant observation and video recording. The research findings showed that there were eleven verbal CSs employed by message senders and six non-verbal. Furthermore, on the learners' strategies to deal with communication problems encountered by message receivers (listeners) were found as many as seven verbal strategies and seven nonverbal strategies Key Words: communication strategies (CSs), EFL Learners, speaking course Abstrak: Penelitian ini mengeksplorasi strategi komunikasi verbal dan nonverbal yang digunakan oleh pembelajar baik sebagai pengirim pesan (pembicara) maupun sebagai penerima pesan (pendengar) untuk mengatasi masalah komunikasi dalam berkomunikasi berbahasa Inggris perkuliahan speaking. Penelitian ini menggunakan desain kualitatif dengan pendekatan etnografi komunikasi dalam situasi terbatas (perkuliahan speaking). Tiga puluh dua mahasiswa yang sedang mengambil mata kuliah speaking II pada jurusan Pendidikan Bahasa Inggris IKIP Mataram, dipilih dengan menggunakan purposeful technique. Teknik pengumpulan data terdiri dari observasi non partisipan dan merekam video. Hasil penelitian menunjukkan bahwa ada sebelas strategi verbal digunakan oleh pengirim pesan (pembicara). Sementara itu, ditemukan enam strategi nonverbal yang diterapkan oleh pembicara dalam mengatasi masalah komunikasi. Selanjutnya, ada tujuh strategi verbal yang diterapkan oleh pendengar dan ada tujuh strategi nonverbal yang diterapkan oleh pendengar: Kata kunci: strategi komunikasi, siswa EFL , pembelajaran berbicara